2006
DOI: 10.1016/j.jnc.2005.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Public choice of species for the ‘Ark’: Phylogenetic similarity and preferred wildlife species for survival

Abstract: The paper reports the findings of an experimental survey conducted to determine the public's willingness to pay for the protection and conservation of the golden-shouldered parrot in Australia. This parrot is endemic to Australia and is one of Australia's most endangered birds. The paper examines the public's knowledge of this parrot and compares it with other endangered birds as well as common birds and the public's willingness to pay for conservation from a hypothetical allocation of money based on their cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 25 publications
4
29
0
1
Order By: Relevance
“…Beyond these findings, other studies have already disclosed a variety of attributes shaping attitudes towards species like for example previous population change, harmlessness, ecological function or phylogenetic similarity to humans (Fischer, Langers, Bednar-Friedl, Geamana, & Skogen 2010;Montgomery 2002;Tisdell, Wilson, & Nantha 2006). Further investigation is therefore needed to determine the relative importance of the invasion criterion among the other attributes playing a role in public opinions of species.…”
Section: Tolerance Towards Invasive Speciesmentioning
confidence: 92%
“…Beyond these findings, other studies have already disclosed a variety of attributes shaping attitudes towards species like for example previous population change, harmlessness, ecological function or phylogenetic similarity to humans (Fischer, Langers, Bednar-Friedl, Geamana, & Skogen 2010;Montgomery 2002;Tisdell, Wilson, & Nantha 2006). Further investigation is therefore needed to determine the relative importance of the invasion criterion among the other attributes playing a role in public opinions of species.…”
Section: Tolerance Towards Invasive Speciesmentioning
confidence: 92%
“…The preference among humans for animal species similar to them has been formalized as the Similar Principle Theory (Plous 1993). This theory is supported by the findings of a research team in Australia, which showed that respondents appeared to favour the survival of mammals rather than birds or reptiles (Tisdell et al 2006). Another study in the United States showed that physical characteristics (e.g.…”
Section: Introductionmentioning
confidence: 95%
“…Most studies have focused on the value given to ecosystems (Balmford et al 2004). Among the few studies that have explored the value given to species, all of them, to our knowledge, have relied on participants' self-reported hypothetical species choices or intentions to support a program (Gunnthorsdottir 2001, Tisdell et al 2006, rather than on their actual behaviour (i.e. real money invested).…”
Section: Introductionmentioning
confidence: 99%
“…The general public and tourists are familiar with some macropod species and regard them as iconic and valued wildlife (Tisdell et al 2005(Tisdell et al , 2006. However, due to their wide-ranging distributions and high mobility, macropods may be especially vulnerable to the disturbances associated with roads (Ramp 2010).…”
Section: Introductionmentioning
confidence: 99%